The influence of emotional intelligence and personal resilience towards university students leadership in Thailand - Numsakulwong, Thawee (2017)
Thailand youths and adolescents having EQ lower than the moderate level, a lack of leadership skills and other practical problems. Interesting student activities have a role to develop many psychological traits. Research survey design cross-sectional study were examined the influence of emotional intelligence and personal resilience on university students’ leadership in Thailand. This quantitative study used 3 instruments, namely Emotional Intelligence inventories (EQ-i), Personal Resilience, and Multi-factors Leadership Questionnaire 6s. 1922 Thai students of 3 public universities in Thailand were sampled through the stratified proportionate technique. Descriptive statistics, t-test, ANOVA and multiple regression were employed to analyze the data, based on the objectives of the study. The result shows that all students mainly had total scores of Emotional Intelligence, five composites and 15 subscales at the average level. All students had personal resilience, and different leadership styles at the moderate level. Variation in the constructs based on the type of students’ participation in activities (participant and non-participant) had a significant difference in emotional intelligence, personal resilience and each leadership style, while gender had a significant difference in personal resilience and transactional leadership. There was a significant difference of laissez-faire leadership among students in different fields of study. There was no significant difference in emotional intelligence, personal resilience and leadership style among the students who studied in different universities and fields of study. The emotional intelligence had a moderate significant relationship with transactional leadership, and a very weak relationship with laissez-faire leadership. Personal resilience had a weak relationship with transactional leadership, and had no significant relationship with laissez faire leadership style. Transformational leadership had a weak significant relationship with transactional leadership, and had no significant relationship with laissez faire leadership. Transactional leadership had a moderate relationship with laissez faire leadership. The conclusion of this research shows that multiples student activities can develop students’ personal resilience and leadership styles through emotional intelligence. The finding contributes the framework to develop students in institutions of higher education.